The Role of Eye Gaze During Natural Social Interactions in Typical and Autistic People - Cañigueral, Roser; Hamilton, Antonia F. de C. (Frontiers in Psychology, 2019)
Social interactions involve complex exchanges of a variety of social signals, such as gaze, facial expressions, speech and gestures. Focusing on the dual function of eye gaze, this review explores how the presence of an audience, communicative purpose and temporal dynamics of gaze allow interacting partners to achieve successful communication. First, we focus on how being watched modulates social cognition and behaviour. We then show that the study of interpersonal gaze processing, particularly gaze temporal dynamics, can provide valuable understanding of social behaviour in real interactions. We propose that the Interpersonal Gaze Processing model, which combines both sensing and signalling functions of eye gaze, provides a framework to make sense of gaze patterns in live interactions. Finally, we discuss how autistic individuals process the belief in being watched and interpersonal dynamics of gaze, and suggest that systematic manipulation of factors modulating gaze signalling can reveal which aspects of social eye gaze are challenging in autism.